Assessing and promoting the use of implementation intentions in clinical practice. (November 2020) - Gonzalez Salas Duhne, Paulina; Horan, Andrew J.; Ross, Caitlin; Webb, Thomas L.; Hardy, Gillian E.
Abstract: Rationale: Striving for goals is a key part of psychological therapy, but people often struggle to translate their goals into action. Prior evidence has found that forming if then plans (or 'implementation intentions') is an effective way to bridge the gap between goals and action. However, it is unclear if therapists naturally prompt their clients to form implementation intentions and, if not, whether training would be feasible. Method and results Study 1: Researchers coded the behavior change techniques used in 40 sessions of therapy for depression using a Cognitive Behavioral Therapy approach and a Person-Centered Experiential Therapy approach and found that therapists do not typically prompt their clients to form implementation intentions in either therapeutic approach. Method and results Studies 2 and 3: The aim was to develop and evaluate a training program for therapists on implementation intentions. Training was delivered face-to-face to 69 cognitive-behavioral therapists (Study 2), and online to 87 therapists working across models (Study 3) and therapists completed self-report measures of their use and knowledge of implementation intentions before training, post-training, and follow-up. The training significantly increased therapists' use and knowledge of implementation intentions. Conclusions: Taken together, these findings suggest therapists can be trained in the use of implementation intentions and that appropriate content might be integrated into training programs. Highlights: Implementation intentions are if-then plans that can help patients achieve their goals. Therapists do not commonly use implementation intentions in their clinical practice. Training for therapists on implementation intentions was acceptable and effective. Online and face-to-face training were similarly effective.